If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 33 = x Reorder the terms: 33 + 12x = x Solving 33 + 12x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 33 + 12x + -1x = x + -1x Combine like terms: 12x + -1x = 11x 33 + 11x = x + -1x Combine like terms: x + -1x = 0 33 + 11x = 0 Add '-33' to each side of the equation. 33 + -33 + 11x = 0 + -33 Combine like terms: 33 + -33 = 0 0 + 11x = 0 + -33 11x = 0 + -33 Combine like terms: 0 + -33 = -33 11x = -33 Divide each side by '11'. x = -3 Simplifying x = -3
| 7(x-7)=-4-16 | | -6.3m+2.7m= | | 0.75x+37-2.75=3(4+x) | | 5x-4=8x+12 | | 0.6x=0.5 | | 13x-8=43 | | 6(3x-1)=5 | | 3p-9=30 | | 14-3s=5 | | 4x-x^4=-4 | | 4x+-3=2x+4 | | 4x-4/5=11/5 | | 5q+4(-7+5q)=1-g | | 5x-8=7x-24 | | 5(x+2)=5x+11 | | 14+4k=-2+2k | | y=2x+-7 | | N/5-6=18 | | 1-x=2/5 | | -4n/4=22/3 | | 3x+6x-9=0 | | 4(2x-4)=8x+-16 | | F(x)=13x+3 | | 4=z/9(4y-2) | | 3s-4=5 | | 2(x-1)(4x+3)=0 | | 2/3x-12=2 | | 4x+80=5x+80 | | 5(x+2)-8x=19 | | x=3x+-2 | | 7q-48+3q+6=180 | | -4(b+8)=-25-5b |